2022
DOI: 10.2147/ijgm.s350783
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Chromobox Family Members: Potential Prognostic Biomarkers and Therapeutic Targets in Head and Neck Squamous Cell Carcinoma

Abstract: Background The Chromobox (CBX) family members were involved in a variety of physiological and oncological processes through the regulation of the epigenetic modification of chromatin. However, the comprehensive analysis of the CBX family in head and neck squamous cell carcinoma (HNSC) is lacking. Methods In this work, we used multiple online databases and tools to investigate the roles of CBX family in aspects of gene expression, prognostic evaluation, genetic alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…These genetic and epigenetic changes lead to the downregulation of CBX7 in BCs. Moreover, loss of CBX7 expression has been reported in primary human tumors of the blood [14], brain [22], head and neck [16], lung [20], skin [17], stomach [21], and ovary [15]. Moreover, the knockout of the Cbx7 gene in mice resulted in the spontaneous development of lung and liver tumors [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These genetic and epigenetic changes lead to the downregulation of CBX7 in BCs. Moreover, loss of CBX7 expression has been reported in primary human tumors of the blood [14], brain [22], head and neck [16], lung [20], skin [17], stomach [21], and ovary [15]. Moreover, the knockout of the Cbx7 gene in mice resulted in the spontaneous development of lung and liver tumors [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed the distinct Integrative Analysis of Genetic and Epigenetic Alterations in the CBX7 Gene Reveals Oncol Insights.2023;2:691 functions among CBX family members in cancer. For example, CBX3 was found to be upregulated, whereas CBX7 was downregulated in many types of human cancer [14][15][16][17][18][19][20][21][22]. Some studies have shown that CBX3 transcriptionally suppresses the p21 gene to promote cell proliferation [23][24][25], while CBX7 transcriptionally suppresses CCNE1 expression to inhibit cell proliferation [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further evaluated the prognostic role of three candidate genes in OC with the help of Kaplan-Meier plotter ( http://kmplot.com/analysis/ ), an online public resource retrieving gene expressions and survival data from public cancer databases such as TCGA for prognostic analysis [ 22 ]. GEPIA2.0 ( http://gepia.cancer-pku.cn/ ) and UALCAN databases ( http://ualcan.path.uab.edu/index.html ) were employed to show the differential mRNA and protein expression of PRNP in OC.…”
Section: Methodsmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSC) is the most common form of head and neck cancer [ 1 ]. HNSC is the sixth most prevalent cancer worldwide [ 2 ]; annually, the number of new cases exceeds 600,000 cases [ 3 ]. HNSCs are malignant tumors of a paranasal sinus, pharynx, larynx, and oral cavity epithelial cells [ 4 ].…”
Section: Forewordmentioning
confidence: 99%